The Development of Effective Christian Leadership through the Integration of Faith, Character, and Competence - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Daniella Beauty Melanesia (Institut Agama Kristen Negeri Manado, 2024)
This study focuses on the development of an effective Christian leadership model by integrating faith, character, and competence as its core pillars. Unlike traditional leadership approaches, this research offers a new contribution by positioning faith in Jesus Christ as the foundation that unites these four elements within a holistic leadership model. Through this approach, Christian leaders are not only guided towards achieving organisational goals but also tasked with bringing a positive spiritual impact to both the workplace and society. The findings of the study indicate that leadership rooted in faith can create lasting influence, foster strong character, and enhance competence in service. This encourages Christian leaders to prioritise eternal values, justice, and transformative service, thereby shaping leadership with broad-reaching impact. The study provides practical guidance for the realisation of relevant and effective Christian leadership in various life contexts.